2000
DOI: 10.1016/s0925-4773(99)00272-5
|View full text |Cite
|
Sign up to set email alerts
|

The Ets family member Erg gene is expressed in mesodermal tissues and neural crests at fundamental steps during mouse embryogenesis

Abstract: The Erg gene belongs to the Ets family encoding a class of transcription factors. To gain new insight on the in vivo functional specificity of the Erg gene within the wide Ets family, we used in situ hybridization to determine its expression pattern during murine embryogenesis. We found that the Erg gene expression predominates in mesodermal tissues, including the endothelial, precartilaginous and urogenital areas. A specific Erg gene expression was also identified in migrating neural crest cells. A comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
66
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 9 publications
8
66
1
Order By: Relevance
“…(42)]. In this study, we showed that ERG, a transcription factor associated with precartilaginous condensation and chondrogenesis preceding bone formation (43,44), binds to the OPN promoter and transactivates this gene. Through EMSA experiments, a functional and conserved cis-regulated enhancer site was localized at nt À118 to À115.…”
Section: Discussionmentioning
confidence: 85%
“…(42)]. In this study, we showed that ERG, a transcription factor associated with precartilaginous condensation and chondrogenesis preceding bone formation (43,44), binds to the OPN promoter and transactivates this gene. Through EMSA experiments, a functional and conserved cis-regulated enhancer site was localized at nt À118 to À115.…”
Section: Discussionmentioning
confidence: 85%
“…It has been characterized as the earliest marker of blood vessels during embryogenesis 14 and has been shown to be expressed in endothelial and mesodermal tissues. 15 Its usefulness as a vascular marker has been demonstrated. 16 Nuclear FLI-1 expression has not been found in normal tissues other than endothelial cells and lymphocytes, but has been detected in Merkel cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The only extramesodermal expression of Erg occurs at E8.5 in migrating neural cells. This expression ceases with settlement and formation of dorsal root ganglia (Vlaeminck-Guillem et al, 2000).…”
Section: An Overview Of the Expression Patterns Of Ets Family Membersmentioning
confidence: 99%
“…During embryogenesis, Erg is also highly expressed throughout the formation of the vascular tree, including both intraand extra-embryonic endothelia (Table 1). Subsequently, endothelial expression decreases until Erg expression is restricted to the forming capillaries of the embryo (Vlaeminck-Guillem et al, 2000). Mesodermal expression of Erg initiates in the branchial arches and extends to the anterior limb bud.…”
Section: An Overview Of the Expression Patterns Of Ets Family Membersmentioning
confidence: 99%
See 1 more Smart Citation